A survey of knowledge-to-action pathways of aging policies and programs in the Arab region: the role of institutional arrangements. (December 2015) - Rizk, Anthony; Kronfol, Nabil; Moffatt, Suzanne; Zaman, Shahaduz; Fares, Souha; Sibai, Abla
Abstract Background While population aging challenges Arab governments to ensure well-being in old age, knowledge translation is gaining support worldwide in evidence-based policymaking and service provision. This study examines the status of existing knowledge translation efforts of aging-related research in Arab countries and evaluates the additional role that institutional arrangements (such as ministry departments, national committees, etc.) play in the relationship between knowledge creation and social and health policies and programs. Methods Data were triangulated from two regional surveys and a supplementary desk review of academic, civil society, ministry, and UN documents. Using a set of indicators, standardized summative indices (out of 100) were generated for five constructs, namely knowledge creation, institutional arrangements, knowledge translation, and health and social policies and programs. Correlations were assessed using Spearman's rank correlation (r s ), and bootstrap multiple linear regression models were used. Results Arab countries scored highest on the institutional arrangements index (median = 69.5), followed by the knowledge creation index (median = 45.9), and lowest on the knowledge translation index (median = 30.2). Both institutional arrangements and knowledge creation significantly correlated with social and health policies and programs. However, when adjusted for knowledge translation, only institutional arrangements retained a significant association with both outcomes (r s = 0.63, p value =0.009 andr s = 0.69, p value =0.01, respectively). Adjusting for institutional arrangements and knowledge creation, the association of knowledge translation with social and health policies and programs was attenuated and non-significant (r s = 0.08, p value =0.671 andr s = 0.12, p value =0.634, respectively). Conclusions There are two key messages from this study. Firstly, institutional arrangements play a central role in aging social and health policy and program development in the Arab region. Secondly, knowledge translation paradigms in Arab countries may be deficient in factors pertinent for promoting evidence-based decision-making and policy-relevant research. These findings call for the need of strengthening institutional arrangements on aging and for promoting knowledge production that meets policy-relevant priorities.